2014
DOI: 10.1080/10426507.2013.858253
|View full text |Cite
|
Sign up to set email alerts
|

Dmap-Catalyzed Synthesis of Novel Pyrrolo[2,3-D]Pyrimidine Derivatives Bearing an Aromatic Sulfonamide Moiety

Abstract: 4-(Nwith benzenesulfonyl chlorides. It was also found that the use of DMAP under solvent-free conditions is much more effective than other catalytic systems such as pyridine as both the catalyst and solvent, t-BuOK in t-BuOH, Et 3 N in ethanol (EtOH), and even DMAP in dimethylformamide (DMF). The influences of the reaction parameters, temperature, and the catalyst amount, on the catalytic performance have been studied. All synthetic compounds were characterized on the basis of their full spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…These findings encouraged us to synthesize some new 4‐imino tetrahydrochromeno[2,3‐ d ]pyrimidine derivatives. Therefore, in continuation of our previous works in the synthesis of new heterocyclic compounds with potential biological activities , in this paper, we report a convenient synthesis of new 3,5‐diaryl‐4‐imino‐5,7,8,9‐tetrahydro‐3 H ‐chromeno[2,3‐ d ]pyrimidines 5a , 5b , 5c , 5d , 5e , 5f , 5g , 5h , 5i through a condensation reaction of 2‐amino‐4‐aryl‐3‐cyano‐5,6,7,8‐tetrahydrobenzo[ b ]pyrans 1a , 1b , 1c , 1d with triethyl orthoformate 2 in boiling acetic anhydride obtaining compounds 3a , 3b , 3c , 3d followed by cyclization with primary aryl amines 4a , 4b , 4c , 4d in the presence of a catalytic amount of triethylamine in refluxing ethanol (Scheme ).…”
Section: Introductionmentioning
confidence: 78%
“…These findings encouraged us to synthesize some new 4‐imino tetrahydrochromeno[2,3‐ d ]pyrimidine derivatives. Therefore, in continuation of our previous works in the synthesis of new heterocyclic compounds with potential biological activities , in this paper, we report a convenient synthesis of new 3,5‐diaryl‐4‐imino‐5,7,8,9‐tetrahydro‐3 H ‐chromeno[2,3‐ d ]pyrimidines 5a , 5b , 5c , 5d , 5e , 5f , 5g , 5h , 5i through a condensation reaction of 2‐amino‐4‐aryl‐3‐cyano‐5,6,7,8‐tetrahydrobenzo[ b ]pyrans 1a , 1b , 1c , 1d with triethyl orthoformate 2 in boiling acetic anhydride obtaining compounds 3a , 3b , 3c , 3d followed by cyclization with primary aryl amines 4a , 4b , 4c , 4d in the presence of a catalytic amount of triethylamine in refluxing ethanol (Scheme ).…”
Section: Introductionmentioning
confidence: 78%
“…Por otro lado, la activación de esta clase de compuestos puede realizarse con un nucleófilo tipo amina; por ejemplo, DMAP. Este compuesto ha sido utilizado ampliamente para muchas reacciones orgánicas, como la reacción de Baylis-Hillman, la síntesis de β-lactamas monocíclicas de N-sulfonilo [37] y de β-cetoamidas a partir de β-cetoésteres [38]. Teniendo en cuenta estos antecedentes, después de obtener los 2-aminoésteres de alquilo bajo irradiación por MW, se evaluó el uso tanto de AlCl 3 como de DMAP, para lo cual se plantearon dos experimentos: en el primero, se preparó una mezcla con DEM, tolueno, AlCl 3 y ácido acético (método A), la cual se dispuso en un tubo de reacción y se irradió bajo MW a diferentes temperaturas (80, 100, 120 y 150 °C) y a diferentes tiempos de reacción.…”
Section: Resultados Y Discusiónunclassified
“…Taking all these facts into consideration, and in conjunction with our earlier studies of synthesis of heterocyclic compounds , herein, we report the synthesis of some new derivatives of 6‐alkylamino‐1,3‐diphenyl‐1 H ‐pyrazolo[3,4‐ b ]pyridine‐5‐carbonitrile 4a–f in synthetically useful yields by Knoevenagel condensation of 5‐chloro‐1,3‐diphenyl‐1 H ‐pyrazole‐4‐carbaldehyde 1 with malononitrile 2 in ethanol containing a few drops of glacial acetic acid at reflux temperature, which afforded compound 3 , followed by cyclization with primary alkyl amines in the presence of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as catalyst in refluxing ethanol (Scheme ). To the authors' knowledge, compounds 4a–f are new and have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%